2007
DOI: 10.7863/jum.2007.26.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Spleen Dimensions in Preterm Infants During the First 3 Months of Life

Abstract: We have provided ultrasonographic spleen volumetric values in preterm neonates and infants during the first 3 months of life, giving reference standards applicable for clinical practice or research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…Literature data on normal values of pediatric splenic dimensions are not univocal. The dishomogeneous ethnic distribution (and probably related health history) of studied pediatric population, consisting prevalently of Nigerian, Indian, and USA children, may influence the variability of the estimation (also due to “normal” exposure to different pathogens) and may limit the generalizability of the data [ 18 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data on normal values of pediatric splenic dimensions are not univocal. The dishomogeneous ethnic distribution (and probably related health history) of studied pediatric population, consisting prevalently of Nigerian, Indian, and USA children, may influence the variability of the estimation (also due to “normal” exposure to different pathogens) and may limit the generalizability of the data [ 18 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reference values for B-mode spleen ultrasound reported in the literature are controversial, with differences depending, at least in part, on the ethnic heterogeneity of studied pediatric populations that include subjects with different ethnic backgrounds, country of origin and residence. Racial differences and interfering genetic or infectious factors may influence spleen size [ 18 – 24 ]. Considering that the spleen volume could greatly influence the results of splenectomy, it is mandatory to have normal values for the pediatric population in the geographic area where the surgical approach is performed.…”
Section: Introductionmentioning
confidence: 99%
“…The liver was measured in the sagittal plane longitudinally in all 5 studies included for liver measurement and ranged from 7 cm 7 in younger patients, to a maximum of 12.1 cm 7 in older patients (Table ), although not all of them used the same technique to measure the liver size (Figure ), and the craniocaudal measurement was the most commonly used . The spleen in all studies was measured in the sagittal plane longitudinally and ranged from 5.2 cm in younger patients, to a maximum of 12.5 cm 7 in older patients (Table ). The right kidney in all studies was measured in the sagittal plane longitudinally, and the reported measurements ranged from 4.5 cm in younger patients, to a maximum of 10.7 cm in older patients (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Normative liver, spleen, and kidney sizes as measured by US change with the child's age, which is expected because of the normal growth and development in a healthy child. Currently published evidence demonstrates that there is no difference in abdominal organ size between boys and girls . However, a correlation was demonstrated between the organ length and the child's weight, height, body mass index, and body surface area, in which patients with a higher weight, height, body mass index, and body surface area tended to have larger organs …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation